Social Participation Differences between SEN and TD Student in Indonesian Inclusive Primary School: A Mixed Method Study - Wilson, Lemuel; Pandia, Weny Savitry S.; Wirastari, Maria (Angstrom Centre of Education, 2024)
SEN students have some characteristics that differentiate them from Typical Development (TD) in social aspects. They tend to have poor social skills and sometimes come up with behavioral problems. Children with TD and sometimes teachers have overall negative attitudes that make their social life even more difficult. This study aimed to prove is there any differences between SEN and TD primary school students’ social participation and factors that influenced it. 252 regular and 30 SEN students involved in a causal-comparative study for four aspects of social participation. Fieldwork used two sociometric questionnaires and a Peer Social Self-Concept instrument. Results indicated that there are differences between social interaction, peer acceptance, reciprocal friendship, and peer social self-concept. Explanatory case studies in two schools with positive and negative social participation revealed that peer acceptance, reciprocal friendship, and social interaction influenced by disabilities type and negative attitude towards SEN. Besides, peer social self-concept influenced exclusively by negative attitudes towards SEN. School management, education about social matters for SEN, TD, and parents expected to improve social participation in SEN.